2019
DOI: 10.1021/acsami.9b03291
|View full text |Cite
|
Sign up to set email alerts
|

Pristine Poly(para-phenylene): Relating Semiconducting Behavior to Kinetics of Precursor Conversion

Abstract: We investigated unsubstituted poly(para-phenylene) (PPP), a long-desired prototype of a conjugated polymer semiconductor. PPP was accessed via thermal aromatization of a precursor polymer bearing kinked, solubility-inducing dimethoxycyclohexadienylene moieties. IR spectroscopy and Vis ellipsometry studies revealed that the rate of conversion of the precursor to PPP increases with temperature and decreases with film density, indicating a process with high activation volume. The obtained PPP films were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The easily evaporable methoxy‐masked para ‐terphenyl makes the use of a sealing‐tube indispensable, in which the leaving‐groups (formally methoxy radicals) are trapped in the vessel and might cause additional side‐reactions. In contrast, no rearrangements were observed for our precursor polymer thin films (Scheme 1 d and e), in which dialkoxylated cyclohexadienylene moieties were thermally aromatized under nitrogen atmosphere and ambient pressure [1–3] . We concluded that aromatization was far more selective in thin films: the precursor polymers PPP syn,pre and PPP anti,pre did not melt in contrast to methoxy‐masked para ‐terphenyl (cf.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…The easily evaporable methoxy‐masked para ‐terphenyl makes the use of a sealing‐tube indispensable, in which the leaving‐groups (formally methoxy radicals) are trapped in the vessel and might cause additional side‐reactions. In contrast, no rearrangements were observed for our precursor polymer thin films (Scheme 1 d and e), in which dialkoxylated cyclohexadienylene moieties were thermally aromatized under nitrogen atmosphere and ambient pressure [1–3] . We concluded that aromatization was far more selective in thin films: the precursor polymers PPP syn,pre and PPP anti,pre did not melt in contrast to methoxy‐masked para ‐terphenyl (cf.…”
Section: Introductionmentioning
confidence: 69%
“…The respective temperatures T arom amounted to 260 °C for 9PP syn,pre and 250 °C 9PP anti,pre , as displayed by sharp exothermic peaks in the DSC profiles accompanied by a mass loss in the thermograms. T arom of the two isomers only differed by 10 °C (250 °C vs. 260 °C), while those of their polymeric counterparts ( PPP syn vs. PPP anti ) deviated more from each other (Δ T arom =55 °C; PPP anti =222 °C vs. PPP syn =277 °C) [1–3] . Both compounds 9PP anti,pre and 9PP syn,pre did neither sublime nor melt in the relevant temperature regime up to 300 °C and thus fulfilled the above‐mentioned criteria for solid‐state aromatization.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In general, the role of bonding in π‐conjugated polymers continues to be an attractive issue, mainly because of recent electron‐transport applications in conducting polymers. [ 16,17 ] Beyond trans ‐PA, which exhibits a 2‐fold ground‐state degeneracy, [ 18 ] renewed interest has been paid to the cases of highly conjugated polymers, exhibiting nondegenerate ground states, for example, poly( p ‐phenylene) (PPP), [ 19,20 ] polypyrrole (PPy), [ 21,22 ] polythiophene (PTh), [ 23,24 ] and other related organic polymers as well. [ 25,26 ] What these systems have in common is a quinoid character in the backbone, [ 3,27 ] which is related to their electronic properties and applications as conducting polymers with tunable band gaps.…”
Section: Introductionmentioning
confidence: 99%